THE SYSTEM OF SOCIAL ASSISTANCE TO ORPHANS IN KAZAN PROVINCE DURING THE ZEMSTVO (LOCAL GOVERNMENT IN RUSSIA) - E. V. Morozova (Вопросы современной педиатрии, 2014)
In this paper we describe a system of charity for orphans in Kazan province during the work of the zemstvo. Analyzed the work of local authorities for the organization of social assistance to children. In keeping zemstvo was handed orphanage, located in a rented room. Already in the first years of the Kazan province zemstvo for these purposes was purchased its own building and taken to hiring additional. This allowed the students to differentiate different age. Deficit funding for social care has led to the fact that since 1896, active distribution system has received the patronage of the family, which means the transfer of children to grow up in farming families with an award from the zemstvo. Although some shortcomings of this system, the number of children prizrevaemyh thus increased annually. By the beginning of the XX century in Kazan province has developed a system of charity childhood, which was based on the rural and private charities. During the years of zemstvo institutions in Kazan province created the conditions for an effective institutions to help children transferred from the Order of public charity, and laid the foundations for the development of a network of institutions charity childhood in the countryside.